(untitled) (Stamford Journal of Microbiology, 2022)
The disease caused by the Dengue virus (DENV), belongs to the Flaviviridae family, which is the most common vector for transmission of the virus between humans and arthropods Aedes aegypti mosquitoes. In recent years, the number of dengue cases has increased drastically throughout the world, according to a survey around 390 million dengue infection cases are recorded annually, among which one-fourth of cases show clinical manifestations. In Bangladesh, dengue outbreaks are on the increasing trend despite the efforts to control this disease A Hospital-based study of dengue patients in Dhaka city was conducted to check the recent trends of dengue infection among the inhabitants of Dhaka, Bangladesh. 89 blood samples from different patients with appropriate symptoms were tested using the Dengue NS1 Quanticard kit. Among samples, 60 (68%) samples were tested as positive whereas 22 (25%) showed negative results and 6 (7%) showed invalid results in tests. Despite the testing of a low number of samples, it can be clearly stated that a large number of positive results was observed with specific symptoms commonly found in Dengue infection. Among all the positive results some (7%) of the patients did not show any signs and symptoms, but after testing the results were positive against the viral antigen. Attempt to increase awareness about dengue fever through effective management measures from the government and NGOs are very much needed. Stamford Journal of Microbiology, Vol.12 (1) 2022: 43-46